Arsitektur Cina dan Akulturasi dengan Budaya Islam sebagai Tema Arsitektur pada Masjid Babah Alun Cilandak Jakarta Selatan - Fitriana, Firda; Dony Putra, Rangga; Arifin, M.; Poltak, Hendrik (Local Engineering, 2026)
The exploration of design themes and concepts is a crucial part of the architectural design process, as both elements shape the characteristics, philosophy, and meaning of an architectural work. Understanding themes and styles poses challenges for designers, particularly in balancing local context with functional, aesthetic, and technological needs. The theme serves as a conceptual direction, while style represents the visual, cultural, and historical expressions of a building. However, confusion between “theme” and “concept” often leads to misapplication, hindering the creation of clear design ideas and objectives. Therefore, a deep understanding of these elements is essential to ensure that design outcomes align with their intended goals and communicate effectively with users. This study aims to examine how architectural themes are applied in design practice through a case study of the Babah Alun Mosque in Cilandak, South Jakarta. The mosque adopts a Chinese architectural theme that is acculturated with Islamic culture, resulting in a unique formal and symbolic expression. This study is expected to enrich the understanding of how themes and concepts interact within architectural design methodologies and contribute to shaping cultural identity in contemporary architectural works.